Rancang Bangun Website Sekolah Menggunakan Google Sites Sebagai Media Informasi dan Komunikasi - Imam Mualim; Rudi Hartono; Ismi Laras Wati; Suci Khotimah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
This study aims to design and develop a school website using Google Sites as an effective medium of information and communication for both the school community and the public. The website development process was carried out through several stages, including needs analysis, content design, page creation, integration of supporting features, and functional evaluation. Google Sites was selected due to its ease of use, design flexibility, and its ability to integrate with various Google services such as Drive, Calendar, and Forms. The results of the development show that the resulting website is capable of providing structured school information, including the school profile, activity programs, administrative services, as well as news and announcement publications. In addition, communication features such as online forms and integrated school contact information enhance accessibility and interaction between the school and users. Based on limited trials, the website was considered feasible and easy to use as an information and communication medium that supports transparency, openness, and effective dissemination of information within the school environment.